Arbitraje y terceros legitimados en la impugnación de acuerdos societarios en el Perú - O’Neill de la Fuente, Cecilia (2020)
In recent years, several national laws have become more favorable to corporate arbitration, which has contributed to its important development. In this context, the arbitrability of the challenge of corporate agreements is widely accepted. However, the intervention of legitimate third parties has resurfaced alleged deficiencies of corporate arbitration.In this article, the authors analyze the topic of legitimate third parties and the solutions proposed in comparative law. They aim to analyze the suitability of those possible solutions with the Peruvian legislation on arbitration and corporations.